Tawhid sebagai Prinsip Primordial Peradaban Islam: Studi Pemikiran Isma’il Raji al-Faruqi - Fadhil Sofian Hadi (Universitas Darussalam Gontor, 2019)
Abstract Ismail Raji al-Faruqi is known as a contemporary Muslim scholar who played an important role and instigator the idea of the Islamization of contemporary science. To realize the idea of the Islamization of contemporary science, al-Faruqi sparked the founding of the International of Islamic Thought (IIIT) centered in the United States. Al-Faruqi is not only well known for his ideas in the arena of thought but also authored a book titled “Al-Tawḥîd: Its Implications for Thought and Life